Ukraiński ruch młodzieżowy w Polsce w latach siedemdziesiątych i osiemdziesiątych XX wieku - Syrnyk, Jarosław (Pamięć i Sprawiedliwość, 2011)
This article is an attempt to make a preliminary analysis of the Ukrainian youth movement in Poland in the 1970s–1980s. Its author points out particular elements of this social phenomenon and simultaneously stresses that its definition still remains an unresolved issue. What is more, he uncovers its eclectic character in which it is possible to distinguish deliberately moderated elements as well as many of those of unknown origin.